Simulation Of IOT Based Domestic Devices By Saving Their State Of Remote Database Server (International Journal of Engineering and Computer Science, 2018)
In this research we have developed a simulation environment where we would switch on /off house hold devices remotely using our web based application through our mobile or laptops. IoT(Internet of Things) allows objects should  be sensed & controlled remotely across existing network infrastructure, create scope for more  integration of physical world into computer-based systems, & resulting in improved effectiveness, accuracy & economic benefit.   The current status of device would be saved in database created by us along with time. A Calculator would calculate power consumption by reading status of devices & time they were kept on/off. The power consumption & battery backup would be computed.